Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
[tex]-3x^2-10x-8 = - (3x^2 +10x+8 ) = - (3x^2 +6x +4x+8) =\\ \\=-[3x(x+2)+4(x+2)]= - (3x+4) (x+2) \\ \\Answer : \ c)\ \ \ -(3x+4)(x+2)[/tex]
[tex]-3x^2-10x-8=-3x^2-4x-6x-8=-x(3x+4)-2(3x+4)\\\\=(3x+4)(-x-2)=-(3x+4)(x+2)[/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.